2018
DOI: 10.1016/j.cyto.2017.07.015
|View full text |Cite
|
Sign up to set email alerts
|

The influence of macrophage growth factors on Theiler’s Murine Encephalomyelitis Virus (TMEV) infection and activation of macrophages

Abstract: Macrophages are common targets for infection and innate immune activation by many pathogenic viruses including the neurotropic Theiler's Murine Encephalomyelitis Virus (TMEV). As both infection and innate activation of macrophages are key determinants of viral pathogenesis especially in the central nervous system (CNS), an analysis of macrophage growth factors on these events was performed. C3H mouse bone-marrow cells were differentiated in culture using either recombinant macrophage colony stimulating factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Microglia and macrophages play a crucial role in the initiation and progression of TMEV-induced demyelination as effector cells and a source of immunomodulatory mediators [21,54,185,186]. The onset of virus-induced demyelination is associated with a dominating polarization of macrophages into pro-inflammatory M1 subtypes, while mounting M2 polarization together with continuous high M1-related gene expression can be found during the chronic-progressive phase [185].…”
Section: Innate Immunity In Theiler’s Murine Encephalomyelitis Virmentioning
confidence: 99%
“…Microglia and macrophages play a crucial role in the initiation and progression of TMEV-induced demyelination as effector cells and a source of immunomodulatory mediators [21,54,185,186]. The onset of virus-induced demyelination is associated with a dominating polarization of macrophages into pro-inflammatory M1 subtypes, while mounting M2 polarization together with continuous high M1-related gene expression can be found during the chronic-progressive phase [185].…”
Section: Innate Immunity In Theiler’s Murine Encephalomyelitis Virmentioning
confidence: 99%
“…After intracerebral infection of susceptible mice with a low neurovirulent TME virus (TMEV) strain (like BeAn), animals develop a biphasic disease that consists of an acute polioencephalitis, followed by a progressive demyelinating leukomyelitis with astrogliosis [25,29,31,32,33]. During the acute phase of TME, virus replication takes place in neurons, whereas the virus resides in oligodendrocytes and microglia/macrophages during the chronic phase [25,29,31,32,33,34]. Mechanisms leading to demyelination in the chronic phase of TME include delayed-type hypersensitivity, bystander demyelination, as well as virus mediated oligodendrocyte death [35,36,37].…”
Section: Introductionmentioning
confidence: 99%
“…The role of GM-CSF in less commonly used models of MS has not been well elucidated. One model that may depend on GM-CSF signaling is the Theiler's murine encephalomyelitis virus-induced demyelinating disease (TMEV-IDD) [77]. Theiler's murine virus is an enteric commensal in most mouse stains; however, when injected via intracranial injection into susceptible mice, such as SJL/J mice, the result is a chronic and progressive demyelinating disease [78,79].…”
Section: Gm-csf In Other Murine Models Of Msmentioning
confidence: 99%
“…One study suggested that GM-CSF may play a role in promoting pathology in this model. Bone marrow cells stimulated with GM-CSF were infected with TMEV, and the presence of GM-CSF was found to promote virus replication and the production of proinflammatory cytokines, indicating that GM-CSF is important in inducing TMEV-IDD [77]. The importance of GM-CSF in this model further highlights the important role of GM-CSF in promoting neuroinflammation associated with immune cell infiltration into the CNS parenchyma, although additional in vivo studies need to be performed to further characterize the role of GM-CSF in this model of demyelinating disease.…”
Section: Gm-csf In Other Murine Models Of Msmentioning
confidence: 99%